1998
DOI: 10.1016/s0092-8674(00)80901-0
|View full text |Cite
|
Sign up to set email alerts
|

Lat

Abstract: Despite extensive study, several of the major components involved in T cell receptor-mediated signaling remain unidentified. Here we report the cloning of the cDNA for a highly tyrosine-phosphorylated 36-38 kDa protein, previously characterized by its association with Grb2, phospholipase C-gamma1, and the p85 subunit of phosphoinositide 3-kinase. Deduced amino acid sequence identifies a novel integral membrane protein containing multiple potential tyrosine phosphorylation sites. We show that this protein is ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
461
0
3

Year Published

1999
1999
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,167 publications
(491 citation statements)
references
References 32 publications
16
461
0
3
Order By: Relevance
“…Interestingly, the adaptors responsible for recruitment of Grb-2/Sos complexes are either resident in the lipid rafts (e.g. LAT; Zhang et al, 1998) or inducibly colocalize in these membrane subregions together with the activated TCR (e.g. Shc; Xavier et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the adaptors responsible for recruitment of Grb-2/Sos complexes are either resident in the lipid rafts (e.g. LAT; Zhang et al, 1998) or inducibly colocalize in these membrane subregions together with the activated TCR (e.g. Shc; Xavier et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other proteins have however been shown to interact with Grb-2 in activated T-cells. Among these, the LAT adaptor is critically required for productive TCR signaling (Zhang et al, 1998). To rule out the possibility that the impaired response to TCR triggering in cells expressing the HA-3FShc-MLS mutant might result from a defect in LAT, the levels of LAT expression and phosphorylation following TCR engagement were determined in these cells.…”
Section: Enhancement Of Tcr Dependent Activation Of the Transcriptionmentioning
confidence: 99%
“…The tyrosine phosphorylated p35±37 proteins were detected in Nck immunoprecipitates only in MCF-7 cells. These proteins were identi®ed as LAT-related (LAT-R) proteins (Zhang et al, 1998) Rac-1 activity is required for FGF-2-induced DNA synthesis Polymerization of actin ®bers was studied by phalloidin TRITC staining in FGF-2 stimulated MCF-7 and MCF-7ras cells. In both cell types, FGF-2 induced actin polymerization at the leading edge of the cellular plasma membrane, provoking extension of lamellipodia and subsequent membrane ru es.…”
Section: Correlation Of Ras Activity and Fgf-2-induced Dna Synthesismentioning
confidence: 99%
“…Surprisingly, in MCF-7 and MCF-7ras cells, we have shown the presence of a constitutive association of Nck with LAT related molecules. LAT expression has been reported in the immune system (Zhang et al, 1998) and has been shown to mediate signaling through the MAPK pathway, PLCg or Rho family GTPases (Cantrell, 1998). Recently, Nck was reported to couple Figure 10 Schematic representation of the transduction pathways involved in FGF-2 mediated mitogenesis in MCF-7 or MCF-7ras cells.…”
Section: Fgf-2 Was Reported To Be Mitogenic For Mcf-7 Cells Under Sermentioning
confidence: 99%
“…The ZAP-70 tyrosine kinase is recruited to the activated complex by binding phosphorylated ITAM motifs via its tandem SH2 domains. Sequential or combinatorial activation of Src family PTKs and the ZAP-70 leads to phosphorylation of many intracellular proteins, including the SH2 domaincontaining leukocyte protein of 76 kDa (SLP-76), the linker for activation of T cells (LAT), and the guanine nucleotide exchange factor Vav, phospholipase C-g1 (PLC-g1), and the protooncoproteins c-Cbl (Jackman et al, 1995;Bustelo, 2000;Park et al, 1991;Weiss et al, 1991;Clements et al, 1998b;Donovan et al, 1994;Weber et al, 1998;Zhang et al, 1998). Two direct consequences of protein tyrosine phosphorylation have been suggested in TCR-mediated signal tranduction.…”
mentioning
confidence: 99%